2014
DOI: 10.1093/czoolo/60.3.392
|View full text |Cite
|
Sign up to set email alerts
|

Age and ovarian development are related to worker personality and task allocation in the ant Leptothorax acervorum

Abstract: In social insects, workers of different morphological castes and age are known to act differently. Yet, it is unclear how body size and ovarian development influence worker personalities (i.e. consistent behavioral variation) and task allocation in similar aged ant workers of monomorphic species. Behavioral variation is thought to be a key element of division of labor, but few studies have linked worker personality to task allocation. We investigated individual behavior in Leptothorax acervorum ant workers at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Whether a worker stays inside the nest and cares for the brood or leaves the nest and forages is strongly influenced by age and physiology with brood carers being younger [3], more corpulent [614] and more fertile [15,16] than foragers. Due to high external mortality outside the nest [17], this age- and physiology-based non-reproductive division of labour is beneficial, because it ensures that young workers with longest residual life span, the largest amount of stored resources and the highest reproductive potential stay inside the safety of the nest.…”
Section: Introductionmentioning
confidence: 99%
“…Whether a worker stays inside the nest and cares for the brood or leaves the nest and forages is strongly influenced by age and physiology with brood carers being younger [3], more corpulent [614] and more fertile [15,16] than foragers. Due to high external mortality outside the nest [17], this age- and physiology-based non-reproductive division of labour is beneficial, because it ensures that young workers with longest residual life span, the largest amount of stored resources and the highest reproductive potential stay inside the safety of the nest.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this prediction, between‐colony differences in collective foraging activity have been linked with colony success in several species of ants (e.g. Kühbandner, Modlmeier, & Foitzik, 2014 , Modlmeier & Foitzik, 2011, Gordon, 2013, Bengston, Shin, & Dornhaus, 2017, Carere, Audebrand, Rödel, & d’Ettorre, 2018). Carere et al (2018) found similar associations between worker deployment and return rates in F. fusca .…”
Section: Discussionmentioning
confidence: 73%
“…Still other contributions delve into the proximate underpinnings of behavior (Shearer and Pruitt, 2014), particularly the role of metabolic rate in guiding individual differences. Finally, the last of the papers herein showcase the emerging interplay between animal personality, social organization, and collective behavior (Kühbandner et al, 2014). This last piece capitalizes on the rapidly growing literature on individualversus colony-level personality in ants Foitzik, 2011, Pinter-Wollman et al, 2012), bees (Wray et al, 2011, Jandt andDornhaus, 2014), and social spiders Riechert, 2011, Pruitt et al, 2013).…”
Section: This Issuementioning
confidence: 88%